Case Report: A rare case of small bowel obstruction secondary to plasma cell myeloma - Bonometti, Arturo; Aronico, Nicola; Santacroce, Giovanni; Fraticelli, Sara; Lucioni, Marco; Cartia, Claudio Salvatore; Vanoli, Alessandro; Latorre, Mario Andrea; Arcaini, Luca; Paulli, Marco; Di Sabatino, Antonio (Frontiers in Oncology, 2022)
Gastrointestinal (GI) involvement of plasma cell neoplasms is extremely rare. Herein, we describe the case of a 74-year-old Caucasian woman who came to our attention with abdominal pain, food vomiting, and weight loss of 10 kg over one year. A computed tomography scan of the abdomen revealed circumferential thickening of terminal ileum, for which the patient underwent an urgent 20 cm-long ileal resection. Histopathological and immunophenotypic analysis revealed a plasma cell neoplasm of the ileum. Subsequent investigations found a serum monoclonal immunoglobulin A component, an osteolytic lesion of the left jaw, and a clonal bone marrow plasma cell infiltrate carrying 1q21 amplification. Given the final diagnosis of plasma cell myeloma (PCM), the patient underwent a VMD (bortezomib, melphalan, and dexamethasone) chemotherapy regimen, achieving a complete remission after a 12-month treatment. For disease relapse, two further chemotherapy regimens were later attempted. At the last follow-up 4 years after the diagnosis, the patient is still alive. This case draws attention to the extramedullary presentation of plasma cell neoplasms, even if rare, as a prompt diagnosis seems to result in a better prognosis. Also, it highlights the relevance of a multidisciplinary approach, involving gastroenterologists, hematologists and pathologists, to the diagnosis and management of these neoplasms.